Biogeography of the cosmopolitan sedges (Cyperaceae) and the area‐richness correlation in plants. (15th June 2016) - Spalink, Daniel; Drew, Bryan T.; Pace, Matthew C.; Zaborsky, John G.; Starr, Julian R.; Cameron, Kenneth M.; Givnish, Thomas J.; Sytsma, Kenneth J.
Abstract: Aim: Across angiosperm families, the area occupied by a family is strongly correlated with its richness. We explore the causes of this area‐richness correlation using the cosmopolitan family, Cyperaceae Juss., as a model. We test the hypothesis that, despite a proposed tropical origin, temperate lineages in the family diversified at elevated rates. We test the hypothesis that the area‐richness correlation is maintained within intrafamilial clades, and that this relationship could be described as a function of niche space. We also test the hypothesis that the partitioning of geographical and ecological space, not the extent of this space, is the factor most closely associated with clade richness. Location: Cosmopolitan. Methods: We use molecular data from four genes sequenced in 384 taxa to develop a chronogram of Cyperaceae. We then develop a model of ancestral ranges and measure rates of diversification throughout the history of the family. Integrating data from over 4, 800, 000 digitized herbarium records, we characterize the range and niche of more than 4500 species and test for correlations of the species richness maintained within clades with range size, range partitioning, range overlap, niche, clade age and rate of diversification. Results: Cyperaceae originated in South America in the late Cretaceous and subsequently dispersed throughout the globe. Of three increases in diversification rate, two occurred in the temperate Northern Hemisphere. The variable most closely associated with clade richness is the partitioning of geographical space by species within each clade. Main conclusions: We show that species‐rich clades in Cyperaceae are not only more widespread, occupy more niche space, and diversify more quickly, but also exhibit patterns that are consistent with the partitioning of geographical and ecological space as a major correlate to diversification.